NEMIS TILIDAGI AKKUZATIV KELISHIGINING QORAQALPOQ TILIDA IFODALANISHI - Abishova, G. (SCIENCE and SOCIETY, 2023)
This article are determined the features of the expression of the German accusative case in the Karakalpak language the methods and grammatical forms are studied in these two cases in unrelated languages.
Keywords: comparative typology; unrelated languages; German; Karakalpak; accusative cases